Use of self‐collected capillary blood samples for islet autoantibody screening in relatives: a feasibility and acceptability study. Issue 7 (8th March 2017) - Liu, Y.; Rafkin, L. E.; Matheson, D.; Henderson, C.; Boulware, D.; Besser, R. E. J.; Ferrara, C.; Yu, L.; Steck, A. K.; Bingley, P. J.; ,
Abstract: Aims: To evaluate the feasibility of using self‐collected capillary blood samples for islet autoantibody testing to identify risk in relatives of people with Type 1 diabetes. Methods: Participants were recruited via the observational TrialNet Pathway to Prevention study, which screens and monitors relatives of people with Type 1 diabetes for islet autoantibodies. Relatives were sent kits for capillary blood collection, with written instructions, an online instructional video link and a questionnaire. Sera from capillary blood samples were tested for autoantibodies to glutamic acid decarboxylase, islet antigen‐2, insulin and zinc transporter 8. 'Successful' sample collection was defined as obtaining sufficient volume and quality to provide definitive autoantibody results, including confirmation of positive results by repeat assay. Results: In 240 relatives who returned samples, the median (range) age was 15.5 (1–49) years and 51% were male. Of these samples, 98% were sufficient for glutamic acid decarboxylase, islet antigen‐2 and zinc transporter 8 autoantibody testing and 84% for insulin autoantibody testing and complete autoantibody screen. The upper 90% confidence bound for unsuccessful collection was 4.4% for glutamic acid decarboxylase, islet antigen‐2 and/or zinc transporter 8 autoantibody assays, and 19.3% for insulin autoantibodies. Despite 43% of 220 questionnaire respondents finding capillary blood collection uncomfortable or painful, 82% preferred home self‐collection of capillary blood samples compared with outpatient venepuncture (90% of those aged <8 years, 83% of those aged 9–18 years and 73% of those aged >18 years). The perceived difficulty of collecting capillary blood samples did not affect success rate. Conclusions: Self‐collected capillary blood sampling offers a feasible alternative to venous sampling, with the potential to facilitate autoantibody screening for Type 1 diabetes risk. What's new?: This is the first study to evaluate the use of capillary blood samples, collected at home by families themselves, for islet autoantibody testing. Capillary sampling was feasible and acceptable in all age groups including young children, with high rates of success in testing for glutamic acid decarboxylase, islet antigen 2 and zinc transporter 8 autoantibodies. The study highlights that insulin autoantibody assays were least likely to be successful, therefore, to avoid missing very young children at risk, second‐line venous sampling may be required in this group. Screening of islet autoantibodies using this method is popular with families of people with Type 1 diabetes, particularly children.